Automatic Generation of 3D Caricatures Based on Artistic Deformation Styles - Benjamin Mora (IEEE Transactions on Visualization and Computer Graphics, 2011)
Caricatures combines humour and art in a visual way. This work demonstrates a fun, semi-automatic pipeline to produce 3D caricatures from photographs, also addressing some of the undesirable 2D artifacts. A pseudo stress-strain model is used to make the caricatures more realistic.